Penerapan Artificial Intelligence (AI) dalam Sistem Administrasi Publik: Peluang, Tantangan, dan Etika Pelayanan Publik di Indonesia - Basron Basron; Adellah Adellah; Naurah Athaya (Universitas 17 Agustus 1945 Semarang, 2026)
Digital transformation in the public sector has encouraged the adoption of Artificial Intelligence (AI) as a strategic instrument to enhance the effectiveness and quality of public service delivery. In Indonesia, the implementation of AI within the public administrative system remains at an early stage and faces various structural, regulatory, and ethical challenges. This study aims to analyze the opportunities, challenges, and ethical implications of AI implementation in Indonesia’s public administration. The research employs a qualitative approach through literature review and policy analysis of governmental digital transformation regulations. The findings indicate that AI holds significant potential to improve bureaucratic efficiency, service transparency, and data-driven decision-making processes. However, regulatory gaps, limited digital literacy among public officials, the risk of algorithmic bias, and data protection concerns constitute major obstacles to its effective implementation. The novelty of this study lies in integrating public administration management analysis with a public service ethics framework grounded in good governance principles within the context of AI implementation in Indonesia. This study recommends strengthening regulatory frameworks for AI in the public sector, enhancing human resource capacity, and developing ethical guidelines for AI utilization to ensure that public services remain accountable, equitable, and oriented toward the public interest.